PENGARUH GRATIS ONGKIR E-COMMERCE SHOPEE TERHADAP KEPUTUSAN PEMBELIAN MAHASISWA PRODI MANAJEMEN UNIMED - Rey Septanislaus Togatorop; Okta Viani Kristin; Serly Sahfitri; Rahel Marito Tambunan; Rachel Stephanie Jovanca Nababan; Nurul Wardani Lubis (Ekonis: Jurnal Ekonomi dan Bisnis, 2026)
This study looks at how Shopee’s free-shipping program influences the buying choices of management students at UNIMED. The research uses a quantitative approach with simple linear regression. One hundred active students who also use Shopee took part in the study, and the data was analyzed using simple linear regression. The results show that the free-shipping feature has a strong positive effect, with a regression coefficient of 0.707 and a contribution of 66.8% to purchasing decisions. This means that the more frequently free-shipping deals are offered, the more likely students are to buy. The program helps lower transaction costs, build customer loyalty, and make buying decisions faster. The findings highlight the importance of using free-shipping promotions as a marketing strategy to attract and keep young consumers..Keywords: Free Shipping, Purchase Decision, E-Commerce, Shopee.